Nanoencapsulation as a General Solution for Lyophilization of Labile Substrates - Girish Vallerinteavide Mavelli (MDPI AG, 2021)
Protein macromolecules occur naturally at the nanoscale. The use of a dedicated nanoparticle as a lyophilization excipient, however, has not been reported. Because biopolymeric and lipid nanoparticles often denature protein macromolecules and commonly lack the structural rigidity to survive the freeze-drying process, we hypothesized that surrounding an individual protein substrate with a nanoscale, thermostable exoshell (tES) would prevent aggregation and protect the substrate from denaturation during freezing, sublimation, and storage. We systematically investigated the properties of tES, including secondary structure and its homogeneity, throughout the process of lyophilization and found that tES have a near 100% recovery following aqueous reconstitution. We then tested the hypothesis that tES could encapsulate a model substrate, horseradish peroxidase (HRP), using charge complementation and pH-mediated controlled assembly. HRP were encapsulated within the 8 nm internal tES aqueous cavity using a simplified loading procedure. Time-course experiments demonstrated that unprotected HRP loses 95% of activity after 1 month of lyophilized storage. After encapsulation within tES nanoparticles, 70% of HRP activity was recovered, representing a 14-fold improvement and this effect was reproducible across a range of storage temperatures. To our knowledge, these results represent the first reported use of nanoparticle encapsulation to stabilize a functional macromolecule during lyophilization. Thermostable nanoencapsulation may be a useful method for the long-term storage of labile proteins.